Celiac artery aneurysm causing an acute abdomen. Issue 4 (21st April 2021) - Castelhano, Rute; Win, Khine Myat; Carty, Sara
Abstract : Abdominal pain is a very common presentation in the accident and emergency department. However, vasculitis is not the usual first differential diagnosis. This paper discusses a case of polyarteritis nodosa presenting with acute abdominal pain alone. Common surgical conditions were obviously considered, but they were not found to cause the patient's problems. We describe how investigations led to this diagnosis discussed in detail in this paper. It is important to remember that prompt recognition of unusual life-threatening conditions can lead to timely intervention.